ANALISA VEGETASI TEGAKAN HUTAN DI AREAL HUTAN KOTA GUNUNG SARI KOTA SINGKAWANG - Haryanto, Dwi Agustian; Astiani, Dwi; Manurung, Togar Fernando (Universitas Tanjungpura, 2015)
Indonesian tropical forest is known for its high diversity and density. Among itâ€™s advetages, urban forest is expected to maintain the forest performance witrh thre opesific diversity and density in order to support this function. Study and analisis on forest inventory was conducted on a 150 ha area of Gunung Sari urban forest on May 2014. The tree analysis was executed with transect method which was represented overall area of Gunung Sari. Results investigated that there were 53 tree species found, included into 26 family, 2 of them are under IUCN red list status, i.e, Alstonia scholaris and Aquilaria malaccensis. It was indicated that overall growth were low, species diversity index was intermediate. In general, forest cover still in good condition with seedlingâ€™s density 150 trees/ha and tree stage 55 trees/ha. Keywords : Abundance index, indexÂ diversity of species, the status of IUCN red list, tree density.